2013
DOI: 10.3758/s13421-013-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Deciding with the eye: How the visually manipulated accessibility of information in memory influences decision behavior

Abstract: Decision situations are typically characterized by uncertainty: Individuals do not know the values of different options on a criterion dimension. For example, consumers do not know which is the healthiest of several products. To make a decision, individuals can use information about cues that are probabilistically related to the criterion dimension, such as sugar content or the concentration of natural vitamins. In two experiments, we investigated how the accessibility of cue information in memory affects whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 60 publications
8
26
1
Order By: Relevance
“…To sum up, our results corroborate previous findings, which show that experimentally manipulated memory accessibility of cue knowledge influences decision processes (e.g., Platzer & Bröder, 2012;Platzer et al, 2014) and generally contribute to ecological models of decision making (e.g., Dougherty, Gettys, & Ogden, 1999;Juslin & Persson, 2002;Marewski & Schooler, 2011;Stewart, Chater, & Brown, 2006) by extending these findings to a frequencybased manipulation of memory accessibility. Our findings indicate that decision makers sample cues in order of fluency when making decisions from memory, at least in settings where a cue hierarchy is not particularly salient.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To sum up, our results corroborate previous findings, which show that experimentally manipulated memory accessibility of cue knowledge influences decision processes (e.g., Platzer & Bröder, 2012;Platzer et al, 2014) and generally contribute to ecological models of decision making (e.g., Dougherty, Gettys, & Ogden, 1999;Juslin & Persson, 2002;Marewski & Schooler, 2011;Stewart, Chater, & Brown, 2006) by extending these findings to a frequencybased manipulation of memory accessibility. Our findings indicate that decision makers sample cues in order of fluency when making decisions from memory, at least in settings where a cue hierarchy is not particularly salient.…”
Section: Discussionsupporting
confidence: 90%
“…The authors found that when cue salience was congruent with cue validity order, the use of take‐the‐best increased, whereas for an incongruent order, the use of compensatory decision strategies prevailed. Platzer, Bröder, and Heck () replicated this finding with verbal materials. In their study, memory accessibility of verbal cues was manipulated visually at the time of retrieval.…”
Section: Introductionmentioning
confidence: 75%
“…This phenomenon in which individuals, while retrieving information from memory, gaze back at spatial locations previously associated with that information (during encoding) has been observed by other studies across different contexts and domains (Johansson & Johansson, 2014;Platzer, Bröder, & Heck, 2014;Renkewitz & Jahn, 2012;Scholz, Mehlhorn, & Krems, 2016;Scholz, von Helversen, & Rieskamp, 2015;Spivey & Geng, 2001). Collectively, these studies suggest that eye movements can be used as a measure of memory retrieval without the need for self-report responses.…”
Section: Eye-movement Measures Of Memory Retrievalsupporting
confidence: 74%
“…In line with the present series of results, the authors also found that participants tended to recall the extreme outcomes (i.e., the largest gains and losses) early in the recall protocol. Finally, Platzer, Bröder, & Heck, 2014 (see also Platzer & Bröder, 2012) showed that a memory-based approach can also explain the decision strategies used in multi-attribute decision-making (MADM). In MADM, information elements of different quality need to be integrated in order to reach a decision or make a choice.…”
Section: Discussionmentioning
confidence: 99%